2009
DOI: 10.1108/14013380910948072
|View full text |Cite
|
Sign up to set email alerts
|

When capital market actors reduce the complexity of corporate personnel and work environment information

Abstract: PurposeThe purpose of this paper is to explore how capital market actors deal with information on personnel and work environment.Design/methodology/approachThe paper uses a qualitative research approach involving interviews with 14 fund managers and two bankers in Stockholm. The empirical analysis is influenced by a combination of system and network theories where social networks are imposed on capital market actors, when they observe corporate information vis‐à‐vis personnel and work environment.FindingsCapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…The results in this study suggest a strong reliance on management when fund managers interpret corporate information consistent with Almqvist and Henningsson (2009). Based on these results, we are not able to discuss further the social agenda surrounding the valuation of a company (Henningsson, 2009).…”
Section: Qrfm 74contrasting
confidence: 61%
See 1 more Smart Citation
“…The results in this study suggest a strong reliance on management when fund managers interpret corporate information consistent with Almqvist and Henningsson (2009). Based on these results, we are not able to discuss further the social agenda surrounding the valuation of a company (Henningsson, 2009).…”
Section: Qrfm 74contrasting
confidence: 61%
“…The results have explorative value and are limited to one area of financial markets, institutional investments, specifically the social context of fund managers. This study contributes to a series of studies and suggestions from the same research area that includes "the idea of a social agenda surrounding the valuation of a company" (Henningsson, 2009) and "the strong reliance on management when reducing corporate information complexity" (Henningsson, 2009;Almqvist and Henningsson, 2009). From a broader financial market social study perspective, the implications of these results become limited and highly tentatively.…”
Section: Discussionmentioning
confidence: 96%
“…They found that information about employees, their working environment and employee satisfaction is least desired, and information about employee‐related investments is not disclosed at all by analysts. Almqvist and Henningsson () argued that analysts exclude the value contribution made by corporate personnel and work environments from their analyses due to the complexity of calculating their worth, but include management quality as a proxy. Prior studies have attributed the limited use of HC information to the lack of information on such measures (Sakakibara et al.…”
Section: Resultsmentioning
confidence: 99%
“…Employers now generally consider a reasonable working environment a prerequisite for legitimacy among the organization's stakeholders (Almqvist & Henningsson, 2009;Frick & Zwetsloot, 2007). Research shows that companies must pay close attention to WHM to prevent sickness and create healthy workplaces (Department of Health, 2004;Holt & Powell, 2015;Lindström, Schrey, Ahonen, & Kaleva, 2000).…”
Section: Previous Research: Whmmentioning
confidence: 99%